(untitled) (Sains Humanika, 2025)
Technological developments, social changes, and unforeseen circumstances have significantly transformed the landscape of school counseling services. Sudden shifts, particularly during the pandemic era, have exposed School Counselors (GBK) to new challenges such as handling technical issues, unstable internet connectivity, and the need to master digital skills. In this context, resilience is a critical element in ensuring the effectiveness of guidance and counseling services, safeguarding psychological well-being, and preventing the risk of work-related burnout. This exploratory qualitative study aims to examine the experiences, challenges faced, and coping strategies employed by GBK in public secondary schools in the district of Johor Bahru. Using purposive sampling, five participants with 15 to 20 years of professional experience were selected. Data were collected through structured interviews and analyzed using thematic analysis. The findings indicate that long-term career experience forms the foundation for building resilience. Seven key factors contributing to resilience were identified: financial stability, support systems, passion for the profession, spirituality, continuous learning, positive thinking, and a sense of responsibility. The study emphasizes that resilience not only influences GBK’s thoughts, emotions, and behaviors but also plays a role in supporting long-term career commitment and enhancing personal well-being. These findings highlight the importance of fostering resilience among educators to strengthen their professional effectiveness and personal well-being.